Dampak Pendapatan Daerah dan Perimbangan Anggaran terhadap Belanja Modal di Kabupaten Bantul - Dwi Setyani; Nugraeni (PT Bone Jaya Kreatif, 2024)
The objectives of this study are 1) to determine the effect of Local Revenue on Capital Expenditure. 2) to determine the effect of General Allocation Fund on Capital Expenditure. 3) to determine the effect of Special Allocation Fund on Capital Expenditure. 4) to determine the effect of Revenue Sharing Fund on Capital Expenditure in Bantul Regency. According to Law Number 32 of 2004, the Regional Revenue and Expenditure Budget acts as a driver and determinant of whether or not regional economic goals and targets are achieved which are directed at overcoming basic problems that are on the community agenda. One of the most important components of the Regional Budget is regional expenditure and the expenditure made should be allocated to public service programs. The research data comes from the official website of the Directorate General of Fiscal Balance with the help of the SPSS program. This research uses quantitative methods, namely the type of research where the information collected is presented in numerical form, starting with data collection and ending with the presentation of research findings in numerical form.Preliminary analysis prerequisite tests include normality test, multicollinearity test, heterocedity test, T test and determination coefficient test. The results of research on the effect of local revenue and equalization funds on capital expenditure in Bantul Regency are 1) Local revenue has a significant influence on capital expenditure of Bantul regency government. 2) Equalization Fund has a significant influence on Capital Expenditure of Bantul regency government.